Assessment of adolescent health conditions in the United Arab Emirates: roles of parental perceptions of the micro and meso built environmental variables - Maghelal, Praveen Kumar (Frontiers in Built Environment, 2025)
IntroductionParent perception and willingness to let their children walk in the arid region of the UAE are impacted by the complexity of environmental factors and children’s own engagement in physical activity. This study, therefore, investigates responses from parents’ perception of the microenvironment, such as sidewalk, streets, traffic, safety, and appeal of the built environment, and meso-environmental factors such as walkability index, traffic exposure at school and residences, and distance to school on the health measured as underweight, normal weight, overweight, and obesity levels of children. MethodsSchool-going children aged 14 to 20 years from seven schools in Al Ain were selected for this study. A survey adapted from the Home Environment Survey (HES), based on the socio-ecological model of physical activity, was administered both in Arabic and English. The outcomes of the health condition measured in four categories based on the BMI were analyzed using multinomial logistic regression. The normal health condition was selected as the base outcome category, with underweight, overweight, and obese, and other outcomes assessed for the study.ResultsGender and physical activity scores predict the obese and underweight categories of the health condition of the adolescents, while age predicts the overweight and obesity in the UAE children. Built environmental factors such as the walkability index, traffic exposure, and distance to school predict overweight and obesity in adolescents. As for parent perceptions, their willingness and perception predict the underweight category, while their education levels predict the overweight and obesity in the adolescents.DiscussionThe health category of adolescents is influenced by a range of factors, including the child's characteristics, built environment at meso and micro levels, and parents’ willingness to let their children walk. Implications for the development of healthy communities and appropriate health policies are discussed in the context of the UAE.